2005
DOI: 10.1073/pnas.0500516102
|View full text |Cite
|
Sign up to set email alerts
|

Richness of plant–insect associations in Eocene Patagonia: A legacy for South American biodiversity

Abstract: South America has some of the most diverse floras and insect faunas that are known, but its Cenozoic fossil record of insects and insect herbivory is sparse. We quantified insect feeding on 3,599 leaves from the speciose Laguna del Hunco flora (Chubut, Argentina), which dates to the early Eocene climatic optimum (52 million years ago) and compared the results with three well preserved, rich, and identically analyzed early-and middle-Eocene floras from the following sites in North America: Republic, WA; Green R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 53 publications
2
105
1
4
Order By: Relevance
“…Smith et al (2012) showed that the Falkland site may be of even higher diversity and proposed that patch dynamics and succession due to landscape-scale disturbance (e.g., area volcanism) may have played a role in generating this diversity. Republic and McAbee were used as the proxy for Northern Hemisphere temperate floras in comparative studies of the highly diverse tropical floras of Early Eocene Patagonia and their relationship to insect diversity (Wilf et al 2003(Wilf et al , 2005Archibald et al 2010Archibald et al , 2013. 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al (2012) showed that the Falkland site may be of even higher diversity and proposed that patch dynamics and succession due to landscape-scale disturbance (e.g., area volcanism) may have played a role in generating this diversity. Republic and McAbee were used as the proxy for Northern Hemisphere temperate floras in comparative studies of the highly diverse tropical floras of Early Eocene Patagonia and their relationship to insect diversity (Wilf et al 2003(Wilf et al , 2005Archibald et al 2010Archibald et al , 2013. 3.…”
Section: Discussionmentioning
confidence: 99%
“…While primarily focused on insects in his study of McAbee, Archibald et al (2010) used rarefaction analysis of a small collection (<200 leaves) to show plant diversity in the Early Eocene comparable to tropical rainforest sites, corroborating an extensive and detailed assessment of insect diversity. These data, in combination with data from Republic (Wilf et al 2003(Wilf et al , 2005 and Falkland (Smith et al 2012) have demonstrated high plant and insect diversity for the Okanagan Highlands fossil sites, which Archibald et al (2010Archibald et al ( , 2013 proposed was caused by low temperature seasonality rather than high tropical-character temperatures.…”
Section: Horsefly Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…Damage diversity on a per leaf basis, as done here and in previous studies, is a core measure of how many ecological feeding types are present on a certain amount of foliage and, because fossil leaves are the units excavated, from a particular amount of sampling effort. This metric is frequency dependent to some extent because a variable proportion of leaves have damage (Wilf et al 2005). However, if undamaged leaves are excluded from diversity analyses to compensate for the frequency dependence, the critical relationship between observed insect damage and the amount of foliage resource available would be lost.…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…Insect herbivory can be measured directly from leaf fossils (Beck and Labandeira 1998;Labandeira 1998;Wilf and Labandeira 1999;Wilf et al 2001Wilf et al , 2005, but the fundamental leaf economic traits that influence herbivory have been difficult to quantify from fossils. Several methods for estimating LL for fossil species exist, but three of these, comparison with nearest living relatives (Chaloner and Creber 1990), leaf thickness (Chaloner and Creber 1990), and presence of leaf mats (Spicer and Parrish 1986), are qualitative; at best they can distinguish deciduous from evergreen leaf habits (e.g., Wolfe 1987;Wolfe and Upchurch 1987).…”
Section: Introductionmentioning
confidence: 99%